2016
DOI: 10.22531/muglajsci.283626
|View full text |Cite
|
Sign up to set email alerts
|

Çam Kozlaklari (Pinus Pinea L.) Kullanilarak Üreti̇len Yongalevhalarin Yangin Performans, Çürüklük Dayanim Ve Yüzey Düzgünlük Özelli̇kleri̇

Abstract: This work explores some technological properties of three-layer particleboard produced from pine (Pinus Pinea L.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Wood is one of the most predominant biomass composites, which has received a lot of attention from the research community due to its renewable nature and innovative applications [1,2]. In wood products, the surface quality of wood has a significant effect on gluing and painting [3], and the basic criterion for surface quality is the surface roughness of wood, and the quality of wood products depends to a large extent on the surface roughness [4]. Studies have shown that the bonding properties and painting of wood products are significantly improved when the surface quality of the wood is higher, i.e., when the surface roughness is smaller [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Wood is one of the most predominant biomass composites, which has received a lot of attention from the research community due to its renewable nature and innovative applications [1,2]. In wood products, the surface quality of wood has a significant effect on gluing and painting [3], and the basic criterion for surface quality is the surface roughness of wood, and the quality of wood products depends to a large extent on the surface roughness [4]. Studies have shown that the bonding properties and painting of wood products are significantly improved when the surface quality of the wood is higher, i.e., when the surface roughness is smaller [5,6].…”
Section: Introductionmentioning
confidence: 99%